2012
DOI: 10.1111/j.1469-7610.2012.02602.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early deprivation on executive attention in middle childhood

Abstract: Background Children reared in deprived environments, such as institutions for the care of orphaned or abandoned children, are at increased risk for attention and behavior regulation difficulties. This study examined the neurobehavioral correlates of executive attention in post-institutionalized (PI) children. Methods The performance and event-related potentials (ERPs) of 10- and 11-year-old internationally adopted PI children on two executive attention tasks, Go/No-go and Flanker, were compared to two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
97
4
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 44 publications
21
97
4
4
Order By: Relevance
“…However, some have questioned whether attentional difficulties among children who experienced institutional rearing are the same as those experienced by noninstitutionalized youth. For example, Loman et al (2013) found that behavior on a Go/No-Go task was more reflective of overall sustained attention deficits among previously institutionalized youth, rather than specifically related to executive attention.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…However, some have questioned whether attentional difficulties among children who experienced institutional rearing are the same as those experienced by noninstitutionalized youth. For example, Loman et al (2013) found that behavior on a Go/No-Go task was more reflective of overall sustained attention deficits among previously institutionalized youth, rather than specifically related to executive attention.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…Research on institutionalized children, which reveals both neural markers of lack of attention/response monitoring, and behavioral inaccuracy in performing a required response, highlights this as a major difficulty in these children (Loman et al, 2013;McDermott, Westerlund, Zeanah, Nelson, & Fox, 2012). Consistent with the two studies just cited, the behavioral performance of institutionalized children in the current study (i.e., error of omission of a response in Go trials, but accuracy in inhibiting a response in No-go trials) reflects difficulties in sustained attention, rather than selective attention or inhibitory control.…”
mentioning
confidence: 99%
“…Adoption demographic predictors, such as institutional caregiving as opposed to foster care (Loman et al, 2013;McDermott et al, 2012;Merz & McCall, 2010;Roy & Rutter, 2006) and adoption from countries with profoundly depriving orphanage care, such as Eastern Europe and Russia (Abrines et al, 2012;Barcons-Castel et al, 2011;Gunnar et al, 2007Gunnar et al, , 2012Lindblad et al, 2010), are consistently linked to a greater risk for inattentive=overactive difficulties.…”
mentioning
confidence: 97%